RELATIONSHIP BUTTERFLY OF DIVERSITY (ORDO LEPIDOPTERA) WITH TROPICAL PLANTS IN THE MURIA MOUNTAIN KUDUS, CENTRAL JAVA - Melisa Oktaviani Sukma; Lianah Lianah; Saifullah Hidayat (UIN Sunan Gunung Djati Bandung, 2021)
The aims of this research is to know relationship betweef butterflies diversity and tropical flower plants in the Muria Mountain at Kudus City of Central Java. The research use quadrat sampling transect method with three stations (along 2 km). Research was conducted in Maret and Juni 2020. The tools used insectnet, termohigrometer, luxmeter, digital camera, rollmeter, GPS, jar and identification book. Data and analyzed for research using Shannon-Wiener index diversity (H’), Evenness index (E), Relative Abundance (Pi), Simpson Dominance Index (D), Density (KR) Frequency (FR), and Important Value Index (IVI). Results of research showed that at least 40 species of 6 family butterflies at Mt. Muria. Survey results of Mt. Muria area has a middle Diversity, middle Evenness, and low dominance. Leptosia nina was the most relative abundance, frequency, density and INP highest species of butterflies. Butterflies were found frequently feeding on flower tropical plants. Two species of flower tropical plants was the most used of butterflies are Lantana camara, and Chromolaena odorata. Mt. Muria was optimal abiotic factors for butterflies habitat.